Efek Samping Obat Antituberkulosis (OAT) Lini Pertama pada Penderita TB Paru di Puskesmas X Kota Bekasi Periode Januari–Maret 2025 - Kamila, Aulia Salasa; Futihat, Chilyati Eky; Arianti, Anisa Rachmita; ., Maifitrianti (LPPM, INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2025)
Tuberculosis is a disease caused by the bacteria Mycobacterium tuberculosis. This disease is still a health problem in the world. The most widely used therapy is First-line OAT. The use of this drug can cause side effects of the drug. The purpose of this study was to determine the side effects of using first-line OAT therapy drugs. This type of study is descriptive observational with a cross-sectional study design. The sampling technique used was consecutive sampling. with inclusion criteria of patients receiving first-line OAT treatment, aged 20-65 years old, patients with intensive or advanced treatment stages, patients with 1 week of treatment then the causality of drug side effects was analyzed using the naranjo algorithm. This study had a sample of 39 respondents who met the inclusion criteria, 62% male patients and 36% aged 20-29 years. As many as 56% were in the intensive treatment phase with the longest treatment duration being 1 month (26%). During the use of first-line OAT, 54% complained of nausea and vomiting, 18% joint pain, 56% red urine, 21% loss of appetite. The results of the causality analysis using the naranjo algorithm showed that the side effects experienced were included in the probable category. The use of first-line OAT in patients with pulmonary tuberculosis can cause side effects. This is stated using the causality analysis of the naranjo algorithm, showing a score of 5-8 (probable) which means the possibility of ESO due to the use of first-line OAT.